Assessing the ethnolinguistic vitality of Pahanan towards developing an instrument for measurement - Peña, Andrew Rey Sosa
This study aims to investigate the factors influencing the ethnolinguistic vitality of Pahanan in order to develop a scale for measuring the ethnolinguistic vitality of Philippine Agta groups. It is a descriptive research that employs indigenous methods of pagtatanung-tanong and pakikiramdam. It used observation, interviews for leaders and individuals and document study to triangulate data gathered from several Pala nan Agta communities.